Evolution of a coquina barrier in Shark Bay, Australia by GPR imaging: Architecture of a Holocene reservoir analog - Jahnert, Ricardo; De Paula, Osni; Collins, Lindsay; Strobach, Elmar; Pevzner, Roman (Elsevier Science BV, 2012)
The Holocene hypersaline carbonate system in Shark Bay, Australia is represented by microbial deposits (stromatolites and thrombolites) and a supratidal coquina beach ridge system which overlies the Pleistocene Bibra Formation and is prograding seaward, since 4500 years ago, over supratidal–intertidal microbial deposits as a consequence of Late Holocene sea level fall, and the high volume of bivalve shells available. The extent, internal architecture and ridge constructional types of coquina deposits in this World Heritage area have not been previously investigated in detail by cores tied with geophysical images. Here we document external and internal architecture of the Holocene coquina system in southeast Hamelin Pool showing three depositional units which comprise the ridge system construction: (1) tabular layers complex, (2) convex-up ridges and (3) washover deposits. Bivalve skeletons represent almost the total amount of bioclasts with symmetrical semi-circular formats and valve sizes 5–9 mm. Based on Ground Penetrating Radar (GPR) images the number of prograding layers present in each transect line varies from 252 to 433, which when compared with the measured 14C ages, shows lateral growth of the system at average rates from 10 years per layer on proximal older sequences to 30 years per layer in the younger and thicker packages which display more gentle inclination and sub-horizontal arrangement. Divergent orientation of tabular layers relates to changes in energy of currents and waves and involves time gaps and erosion. After earliest crest construction the system experienced a decrease in sea level (3600–3000 14C years BP) that left behind a sequence of parallel tabular layers with dip angles (> 10° to < 20°) which accreted seaward as the first major prograding event.The accretionary tabular layers progressively lost height till near 3000 years BP, representing continuous relative SL and storm energy fall, when the first major swale was constructed. Between 2000 and 3000 years BP a series of events constructed 4 large convex-up crests separated by swales overlying tabular layers. Marked changes in layer arrangement occurred since 1000 years ago when subsequent to erosional events the coastal system rearranged and is characterized by layers with low dip angle (< 10°). The Shark Bay ridge system represents the results of waves, surges and swash during storm activity and subsequent reworking history of eroded material in a context of continuous sea level fall. Alternating beach ridges and swales represent events of storm intensity variation during falling late Holocene SL. This progradational model of coquina ridge construction at Shark Bay is a useful analog for ancient coquina reservoirs deposited in lacustrine systems, since the hydrodynamic setting and semi-closed environment affected by storms is similar to some ancient examples such as the coquina reservoirs in the Campos Basin, Brazil.